PERANCANGAN APLIKASI ANDROID REKAPITULASI HASIL PEMILU SEMENTARA MENGGUNAKAN ALGORITHMA SEQUENTIAL SERCING BERBASIS MOBILE - Latifah, Fitri; Abimanyu, Ari Setiawan (Jurnal Techno Nusa Mandiri, 2016)
n the conventional process of recapitulation of the ballot by collecting data from TPS to the village, then the sub-district, district to the Central Election Commission. The process is so lengthy and very time-consuming. With this application input data, the vote counting at polling stations in question for each candidate or candidate performed directly in a mobile polling station concerned when the counting of votes at the polling process is completed. The process of data storage from the user application to the database server using JSON data exchange methods are relatively mild. In addition, the presentation of data recapitulation ballot conducted while officially takes a long time because of the lengthy process of collecting ballots also from TPS to the Central Election Commission. The design of applications that the authors have developed will make it easier to see the results in real recapitulation in text and graphics. Presentation of the recapitulation comes to the data that resides on the database server that always accumulates each input data from each polling station entrance.